How Epstein-Barr virus envelope glycoprotein gp350 tricks the CR2? A molecular dynamics study - ÖZBEK SARICA, PEMRA (My University, 2022)
© 2022 Elsevier Inc.The connection of Epstein Barr virus (EBV) with diseases such as Burkitt Lymphoma, Hodgkin disease, multiple sclerosis, systemic lupus erythematosus and various B-cell lymphomas made EBV glycoproteins one of the most popular vaccine immunogens. As a protein being encoded by EBV, the viral membrane envelope protein gp350 is studied extensively due to its abundancy on the surface and its interaction with complementary receptor, CR2. The binding of CR2 and gp350 not only leads to the entrance of the virus to the B-cells, but also prevents CR2 and C3d protein interactions that are required for immune response. Thus, understanding the inhibition of gp350 activity is crucial for vaccine development. Although, the active residues on gp350 structure were determined by several mutational studies, the exact mechanism of CR2 binding is still not clear. To this end, we have performed molecular docking followed by molecular dynamics simulations and MM-PBSA on wildtype and several mutated gp350 and CR2 structures. Apart from identifying crucial amino acids, the results of per-residue decomposition energy analysis clarified the individual energy contributions of amino acids and were also found to be accurate in differentiating the active site residues in CR2 binding. Here, we highlight the role of binding region residues (linker-1) but more interestingly, the dynamic relation between the distant sites of gp350 (linker-2 and D3 residues) and CR2. These findings can lead further vaccine development strategies by pointing to the importance of computationally found novel regions that can be potentially used to modulate gp350 activity.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Malzeme Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; SPEKTROSKOPİ; KİMYA, FİZİKSEL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; MATERIALS SCIENCE; CHEMISTRY; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; MATERIALS SCIENCE, MULTIDISCIPLINARY; SPECTROSCOPY; CHEMISTRY, PHYSICAL; Fizik Bilimleri; Fiziksel ve Teorik Kimya; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Malzeme Kimyası; Physical Sciences; Physical and Theoretical Chemistry; Computer Graphics and Computer-Aided Design; Materials Chemistry; Molecular dynamics simulations; Molecular docking; Epstein barr virus (EBV); Envelope proteins; gp350; Type II complement Receptor (CR2); Viral vaccines; SYSTEMIC-LUPUS-ERYTHEMATOSUS; BINDING-SITE; FORCE-FIELD; COMPLEMENT; RECEPTOR; C3D; EBV; IDENTIFICATION; ANTIBODY; DOMAIN